Practical Training as A Basis for The Organization of Training in Mathematics - Anvar Jumanazarovich Khurramov (Zien Journals, 2021)
In this article, practical training is one of the forms of teaching aimed at expanding the knowledge gained in the lectures, as well as improving the scientific materials and skills in the subject being taught. It has been scientifically revealed that the effective organization of practical lessons in mathematics depends on the skills of the teacher
Keywords: Training; practical training; scientific materials; lectures